The Effect of The Application of Auditory Intellectually Repetition (AIR) Learning Model on the Ability to Understand Mathematical Concepts Reviewed from Mathematical Logic Intelligence in Learners - Naufal Qadri Syarif,; Ulfiani Rahman,; Fitriani Nur,; Suharti,; Andi Mattoliang, Lisnasari (Alauddin Journal of Mathematics Education, 2022)
This study aims to find out the differences: the ability to understand mathematical concepts using auditory intellectually repetition (AIR) learning models and conventional learning models and students' mathematical concept comprehension ability in terms of mathematical logic intelligence and the influence of interactions between intellectually and repetition (AIR) learning models and mathematical logic intelligence on the ability to understand mathematical concepts. This research is a quasi-experiment with the design of a nonequivalent control group design. Students of class VIII MTsN 1 Makassar City are the population of this study. Sample determination is carried out by means of simple random sampling. The ability test for understanding mathematical concepts and the questionnaire of mathematical logic intelligence of students are the instruments used in this study. The analysis techniques in this study used descriptive statistical analysis and inferential statistical analysis. Based on the results of the analysis obtained (1) there is a difference in the ability to understand mathematical concepts between the application of the Auditory Intellectually and Repetition (AIR) learning model and the conventional learning model of class VIII MTsN 1 Makassar City students (2) there are differences in the ability to understand mathematical concepts in terms of mathematical logic intelligence of class VIII MTsN 1 Makassar City students (3) tidak terdapat pengaruh interaksi antara model pembelajaran Intellectually and Repetition (AIR) dan kecerdasan logika matematik terhadap kemampuan pemahaman konsep matematika siswa kelas VIII MTsN 1 Kota Makassar.